The relationship between academic qualification and teaching experience towards preschool teacher self-efficacy on carrying out teaching and facilitation during post Covid-19 pandemic - Hanassia Andoh; Connie Cassy Ompok; Nur Suhaidah Sukor (Malaysian Journal of Social Sciences and Humanities (MJSSH), 2010)
The purpose of this study was to identify the relationship between academic qualification and teaching experience towards preschool teacher self-efficacy on carrying out teaching and facilitation during post covid-19 pandemic. Sample size (n=74) are fixed based on Krejcie-Morgan sampling size formula (1970), respondents are selected randomly amongst preschool teacher from The Department of Regional Development (KEMAS) in Ranau district. Raw data obtained through questionnaire, which utilize the Teacher’s Sense of Efficacy (TSES) by Tschannen-Moran & Hoy (2001), and analyzed by SPSS v20.0. Descriptive analysis showed that, teacher self efficacy were at medium high level whereas M=3.69, SD=0.59. Pearson Correlation shows unsignificant relationship between academic qualification and teaching experience towards teacher efficacy as K>.05 for both variables. This finding indicates that teacher sense of efficacy to carry out teaching and facilitation in class amid post Covid-19 pandemic is not determined by academical qualification and teaching experience. However, by looking through domain of efficacy, it shows that teaching experience do correlate with efficacy in class management whereas r=.236, k<0.05.